Bringing Personality Into the Public Health Conversation: Evidence From a Correctional Population. (October 2019) - Dumont, Dora M.; Brousseau, Christine; Shuford, Sarah Hart; van den Berg, Jacob J.; Stein, L. A. R.; Clarke, Jennifer G.
Incarceration provides an opportunity for public health interventions, but communication and the delivery of services are complicated by considerable variability even within this generally high-needs population. Public health practitioners have relied heavily on social determinants of health data in their work, but this does not fully explain key patterns in responses and success. Psychometric work related to the "big five" or "five-factor" personality domains may provide important additional guidance to health communications and interventions. The Contraceptive Awareness and Reproductive Education clinical trial provided health risk factor and personality data on 257 incarcerated women aged 18–35. Of the study population, 85.9% reported at least one of the five forms of childhood trauma. Three of the five personality domains were associated with multiple health risk factors and four of the five were associated with fair or poor general health. Personality data provide important guidance in understanding variability in responses to public health interventions in the correctional setting.